Adaptive Leadership Model of School Principals in Improving Education Quality under the Kurikulum Merdeka - Slamet Riyadi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This article examines how adaptive leadership practices enacted by Indonesian school principals contribute to improving education quality within the implementation of Kurikulum Merdeka. Kurikulum Merdeka is a national curriculum reform that grants schools and teachers greater flexibility to design learning, emphasizes essential content, and promotes project-based learning to strengthen the Profil Pelajar Pancasila. Anchored in adaptive leadership theory, the study employs a qualitative phenomenological approach to explore principals’ lived experiences in navigating complex curricular changes, resource constraints, and heterogeneous learner needs. Data are conceptualized as in-depth narratives from principals, vice-principals, and senior teachers in basic education settings implementing Kurikulum Merdeka. Thematic analysis, informed by Miles and Huberman’s interactive model, generates an integrative model comprising four dimensions of adaptive principal leadership: diagnosing contextual and curricular challenges, orchestrating teacher learning, reconfiguring school structures and resources, and cultivating collaborative learning communities. These practices align with prior Indonesian evidence that principal leadership significantly shapes teacher quality, instructional practices, and school effectiveness. The article concludes with theoretical and practical implications for leadership preparation, district support, and policy design to strengthen adaptive capacity of school leaders under Kurikulum Merdeka.